Tragedy without the Tragic: Why Conspirational Narrative Mirrors Our Society (ENTHYMEMA, 2024)
The diffusion of unconventional communication channels – mainly social networks – raises concerns about the manipulative and propagandistic opportunities connected with the power of storytelling in general and the emergence of the so-called conspirational narrative. In this essay, we try to understand its structure by pointing out how our society shows all the symptoms of what Girard called “the sacrificial crisis” (the frantic search for a scapegoat and widespread prophetic spirit). However, despite this crisis, the emerging storytelling often fails to meet a tragic narrative scheme that could open the possibility of a catharsis-healing for the recipient. Instead, it remains trapped in a strongly polarized narration that characterizes the commonly so-called conspirational interpretation of reality and the counter-arguments in defense of the establishment deemed demystifying and scientific. This narration mirrors our political and imaginative regression caused by our inability to think of a future outside of the capitalist system, of which imbalances are perceived as natural and unavoidable.
Keywords: Gottschall; Storytelling; Conspiracy Theory; Tragedy; Limit